32. FACTORS ASSOCIATED WITH THE EXPERIENCE OF PATIENTS UNDERGOING GASTROINTESTINAL ENDOSCOPY AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze factors associated with the experience of patients undergoing gastrointestinal endoscopy at Vinmec Times City International General Hospital in 2025.Subjects and methods: A cross-sectional descriptive study was conducted on 360 outpatients indicated for gastrointestinal endoscopy at Vinmec Times City International General Hospital from January to July 2025. The Gastrointestinal Endoscopy Satisfaction Questionnaire (GESQ) was used to assess patients’ positive and suboptimal experiences. The Chi-square test was applied to examine associations, with statistical significance set at p < 0.05.Results: A lower education level (≤ high school) was associated with a poorer experience regarding pre-endoscopy information. Factors associated with suboptimal experiences in technical skills and hospital-related aspects included age > 60 years, a history of previous endoscopy, and undergoing therapeutic procedures during endoscopy. Poorer experiences related to pain and discomfort during and after the procedure were associated with not receiving sedation and having therapeutic interventions performed. The overall endoscopy experience was also negatively associated with undergoing therapeutic procedures. All associations were statistically significant with p < 0.05.Conclusions: Several factors associated with the patient experience in gastrointestinal endoscopy include education level, age, history of endoscopy, procedure performance, and anesthesia.
Keywords: Factors associated with experience, gastrointestinal endoscopy patients.